2022
DOI: 10.1186/s12935-022-02613-y
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF upregulates the expression of aquaporin-9 through CEBPB to enhance the cytotoxic activity of arsenic trioxide to acute myeloid leukemia cells

Abstract: Background Arsenic trioxide (ATO) is highly effective in acute promyelocytic leukemia (APL) patients, but it fails to show satisfactory efficacy in other acute myeloid leukemia (AML) patients with non-APL subtypes. Different from the APL cells, most non-APL AML cells express low levels of the ATO transporter Aquaporin-9 (AQP9) protein, making them less sensitive to ATO treatment. Recently, we found that granulocyte colony stimulating factor (G-CSF) can upregulate the expression of AQP9. We hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…38 Previous studies [39][40][41] have primarily focused on the critical role of CEBPB in cellular senescence. However, several studies [42][43][44] have also observed an association between CEBPB and pro-apoptotic processes. In our study, we demonstrated that high-dose short-term arsenic exposure up-regulates the expression of CEBPB, promoting cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Previous studies [39][40][41] have primarily focused on the critical role of CEBPB in cellular senescence. However, several studies [42][43][44] have also observed an association between CEBPB and pro-apoptotic processes. In our study, we demonstrated that high-dose short-term arsenic exposure up-regulates the expression of CEBPB, promoting cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro study 44 have found that CEBPB is involved in arsenic trioxide‐induced endoplasmic reticulum stress‐mediated apoptosis. In addition, a recent study 43 discovered that granulocyte colony‐stimulating factor up‐regulates the expression of aquaporin‐9 through CEBPB, enhancing the pro‐apoptotic ability of arsenic trioxide in acute myeloid leukemia cells. These studies provide further evidence supporting the crucial role of CEBPB in arsenic‐induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the greater part of non-APL AML cells presents small concentrations of the ATO transporter AQP9 protein, making them less responsive to ATO administration. Lately, an experiment showed that granulocyte-colony stimulating factor (G-CSF) can increase the expression of AQP9 [ 81 ]. The authors supposed that the administration of G-CSF may foster the antileukemic action of ATO in non-APL AML cells.…”
Section: Aqps and Hematological Malignanciesmentioning
confidence: 99%
“…Moreover, an experiment demonstrated that the increase in AQP9 by G-CSF is due to the transcription factor CCAAT enhancer binding protein beta (CEBPB). Interestingly, the study reported that the combined use of G-CSF and ATO remarkably reduced tumor proliferation in a xenograft animal model [ 81 ]. Therefore, the combined employment of G-CSF and ATO increasing AQP9 concentrations would be a possible therapeutic option for AML subjects.…”
Section: Aqps and Hematological Malignanciesmentioning
confidence: 99%
“…A positive correlation of AQP9 expression and ATO-induced cytotoxicity has been described for 10 out of 11 myeloid and lymphod cell lines [ 20 ]. Upregulation of AQP9 by G-CSF or Azacytidine enhanced the effect of ATO in non-APL AML cells [ 19 , 21 ]. In addition, several other arsenic-based combination studies, including ATO-tyrosine kinase inhibitor combinations, have been conducted in vitro and in vivo with the aim of overcoming ATO-resistance in non-APL AML cells [ 13 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%